2021
DOI: 10.48550/arxiv.2101.03146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G_a^{perf}-modules and de Rham Cohomology

Abstract: We prove that algebraic de Rham cohomology as a functor defined on smooth Fp-algebras is formally étale in a precise sense. To prove this, we define and study the notion of a pointed G perf a -module and its refinement which we call a quasi-ideal in G perf a following Drinfeld. Our results show that given de Rham cohomology, one obtains the theory of crystalline cohomology as its unique functorial deformation.1. We reduce the problem to the case where the base Artinian local ring A is F p [ǫ]/ǫ 2 . 2. Given an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the above t is required to be a G a -module map once the target is given the appropriate G a -module structure via restricting scalars along ϕ. In order to understand the map t , we can therefore apply graded Cartier duality [Mon21,§2.4]. We note that W [F ] * = G a and thus we get a map of graded group schemes t * : G a → G a , where the source group scheme G a receives its grading via the G a -module structure induced by restriction of scalars along s. By easy degree considerations, it follows that there exists a unique G amodule map t which fits into the above commutative diagram.…”
Section: Endomorphisms Of De Rham Cohomology IImentioning
confidence: 99%
See 2 more Smart Citations
“…In the above t is required to be a G a -module map once the target is given the appropriate G a -module structure via restricting scalars along ϕ. In order to understand the map t , we can therefore apply graded Cartier duality [Mon21,§2.4]. We note that W [F ] * = G a and thus we get a map of graded group schemes t * : G a → G a , where the source group scheme G a receives its grading via the G a -module structure induced by restriction of scalars along s. By easy degree considerations, it follows that there exists a unique G amodule map t which fits into the above commutative diagram.…”
Section: Endomorphisms Of De Rham Cohomology IImentioning
confidence: 99%
“…From a technical point of view, in certain situations, showing that the de Rham cohomology functor has no nontrivial automorphisms has been used as a key tool in [BLM20] and [LL21] to prove that certain constructions are functorially isomorphic. Further, in [Mon21], it was shown that one can reconstruct the theory of crystalline cohomology as the unique deformation of de Rham cohomology theory viewed as a functor defined on smooth F p -schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 9.4. Theorem 9.3 has very recently been generalized by Mondal [103]: de Rham cohomology of 𝔽 𝑝 -algebras admits a unique deformation over any local Artinian ring with residue field 𝔽 𝑝 (coming from the base-change of crystalline cohomology). Mondal's work relies on some of the stacky ideas studied by Drinfeld [45].…”
Section: The Motivic Filtrations For Quasi-regular Semiperfect 𝔽 𝒑 -A...mentioning
confidence: 99%